Analysis of the purchasing behaviour on skin care products among the younger generation / Fong Shieng Yee and Susan Chin Tee Suan - Fong, Shieng Yee; Chin, Susan Tee Suan (2012)
The purpose of this study is to analyse the purchasing behaviour of the younger generation on skin care products. A total of 200 respondents took part in this survey. From the analysis, it was found that Environmental Concerns was ranked the highest among the six variables chosen for the study. The other remaining variables are price, packaging, promotion, branding and self Image.